Development of bioceramic bone scaffolds by introducing triple liquid phases. Issue 22 (11th October 2016) - Shuai, Cijun; Duan, Songlin; Wu, Ping; Gao, Dan; Feng, Pei; Gao, Chengde; Peng, Shuping
Abstract: Abstract : In this study, a system of triple liquid phases was developed using Li2 CO3, Na2 CO3, and K2 CO3 to improve the densification of the akermanite scaffolds fabricated by selective laser sintering (SLS). The system formed a ternary liquid phase (Li2 CO3 –Na2 CO3 –K2 CO3 ) at 399 °C, a binary liquid phase (Na2 CO3 –K2 CO3 ) at 695 °C, and a unitary liquid phase (K2 CO3 ) at 891 °C during sintering process. The effects of the liquid phases on the sinterability and mechanical properties of the scaffolds were investigated. The fracture toughness and compressive strength is increased by 43 and 152% with liquid phases increasing from 0 to 4 wt%, respectively. This was explained that liquid phases enhanced densification via improving diffusion kinetics and inducing particle rearrangement. In addition, the scaffolds maintained favorable hydroxyapatite (HA) formation ability and cell proliferation ability, which was proved by simulated body fluid (SBF) test and microculture tetrazolium test (MTT), respectively.